Musik sebagai Instrumen Sosial dalam Pembentukan PerilakuKewarganegaraan di Sekolah Dasar - Ridwan Ardi (FKIP UNSULTRA, 2025)
Music is a form of cultural expression that not only plays a role in developing aesthetics, but also as an educational medium that can instill social and civic values ​​in students. This study aims to examine the literature on the role of music as a social instrument in shaping civic behavior in elementary schools. Through a search of academic sources from national and international journals over the past five years, it was found that music can encourage attitudes of empathy, cooperation, appreciation of differences, and active participation in the social environment. Music in the form of singing, rhythmic games, and collaborative art projects has proven effective in instilling Pancasila values ​​and national spirit. Music learning associated with the theme of diversity and love for the country also encourages the creation of an inclusive classroom environment. This study concludes that music can be a strategic medium for internalizing civic values ​​in a fun and meaningful way. The implication of this study is the need for music integration into the civic education curriculum in elementary schools as an affective approach that strengthens students' social competence.